Melioidosis with venous thrombosis and cellulitis in the left lower limb: a case report - Anik Palit; Mahmudur Rahman; Md. Mahfuzer Rahman; Zubair Akhtar; Mohammed Ziaur Rahman; Muntasir Alam; Arpita Shyama Deb; Sukanta Chowdhury; Md. Mahfuzur Rahman; Pritimoy Das; Fahmida Chowdhury; Tanzir Ahmed Shuvo (Journal of Medical Case Reports)
Abstract Background Melioidosis, which is caused by Burkholderia pseudomallei, is a disease with a high case fatality rate and a wide variety of disease manifestations causing diagnostic dilemmas for medical professionals. Risk factors such as diabetes contribute to a worse prognosis if not treated with appropriate antibiotics during the course of management. This case report describes a diabetic melioidosis case with a rare presentation of venous thrombosis of the lower limb and a successful course of treatment. Case presentation The patient was a 48-year-old Bangladeshi male who was admitted with gradually increasing left knee pain and intermittent high-grade fever for 7 days. On examination, he had a palpable spleen, high body temperature (102 °F), and pitting edema in the left lower limb during admission. He was treated with empiric meropenem on admission considering his serious illness. Doppler ultrasound of the left lower limb revealed superficial venous thrombosis and thrombophlebitis involving the long saphenous vein and superficial veins of saphenous territory below the knee. The patient was enrolled as an eligible case in a research study called the Acute Febrile Illness study. Blood culture confirmed the diagnosis as melioidosis. Doxycycline was added to his treatment regimen when the research study team informed the treating physician at the hospital about the diagnosis of melioidosis. He was discharged with cotrimoxazole, which was advised to be taken for 3 months. Conclusion This case report shows us the lack of diagnostics to detect melioidosis in hospital settings in Bangladesh. The successful treatment outcome proved the importance of routine surveillance for rare or unusual diseases, in addition to endemic pathogens. In addition, training is essential to improve knowledge and raise awareness among clinicians about the clinical diagnosis and management of melioidosis.